A NEW SPECIES OF GYROCHEILOS (GESNERIACEAE) FROM VIETNAM. (1st July 2015) - Middleton, D. J.
Abstract : The new species Gyrocheilos orbiculatum D.J.Middleton (Gesneriaceae) is described and illustrated.